INTERBANK CONTAGIOUS: SISTEMIK MARKET RISK KASUS PADA PERBANKAN INDONESIA 2002-2012 - Christiawan, Nicolaus Gerry; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2013)
Every bank has their eternal risk, which is maturity mismatch. Those risk caused bybank’s business core. The maturity mismatch can cause the bank failure and also can trigger the contagion effect. This study focus on interbank contagion effect problem and potential of systemic risk phenomenon in Indonesia’s banking industry in period 2002-2012. In this case in order to understand the contagion effect and systemic risk potential there are a few analysis’ to test the contagion existence, there are tracking on interbank contagion pattern, measuring the impact of interbank contagion effect on banking industry, measuring respond period of interbank contagion effect.Vector Autoregression are the method that selected in this study to analyze the contagion effect on sample that consist of bank that had 8,9 trillion rupiah minimum total asset in 2011(Indonesian top ten biggest bank on asset). The reason why those ten are being chosen is those ten held 63% of total banking industry asset in Indonesia. In order to describe the interbank contagion effect, financial distress contagion index being used. The index being composed by three variable which are current account in other bank divided by third-party funds ,the difference between fair value of financial asset divided by totalasset, difference between foreign exchange transaction divided by total asset. In this VAR Analysis model there are three methods that had selected which are: Granger causality test, VAR analysis, impulse respond function (IRF).Conclusion form this Interbank Contagion: Systemic Market Risk in Indonesian banking Industry 2002-2012 study, there is systemic risk and also contagion risk in Indonesian Banking Industry. This is showed by the provement of all of the hipothesis in data analysis. From the data analysis result, the pattern of contagion effect, size of contagion impact, and quickness of the responses can be showed. However, the impact of systemic crises that may happen is not significant enough to collapsing the whole Indonesia’s banking industry.